Uterine natural killer cells initiate spiral artery remodeling in human pregnancy - Robson, Andrew; Harris, Lynda K; Innes, Barbara A; Lash, Gendie E; Aljunaidy, Mais M; Aplin, John D; Baker, Philip N; Robson, Stephen C; Bulmer, Judith N (The FASEB journal, 2012)
Uterine spiral artery remodeling is required for successful human pregnancy; impaired remodeling is associated with pregnancy complications, including late miscarriage, preeclampsia, and fetal growth restriction. The molecular triggers of remodeling are not known, but it is now clear that there are "trophoblast-independent" and "trophoblast-dependent" stages. Uterine natural killer (uNK) cells are abundant in decidualized endometrium in early pregnancy; they surround spiral arteries and secrete a range of angiogenic growth factors. We hypothesized that uNK cells mediate the initial stages of spiral artery remodeling. uNK cells and extravillous trophoblast (EVT) cells were isolated from early pregnancy decidua and placenta. Chorionic plate arteries from full-term placentas and spiral arteries from nonpregnant myometrium were cultured with angiogenic growth factors or conditioned medium (CM) from uNK cells or EVT or uNK cell/EVT cocultures. In both vessel models, uNK cell CM induced disruption of vascular smooth muscle cells (VSMCs) and breakdown of extracellular matrix components. Angiopoietin (Ang)-1, Ang-2, interferon-γ, and VEGF-C also disrupted VSMC integrity with an Ang-2 inhibitor abrogating the effect of uNK cell CM. These results provide compelling evidence that uNK cells contribute to the early stages of spiral artery remodeling; failure of this process could contribute to pregnancy pathology.